Programming of skilled football players training process in the second cycle of specially created training during the year - Kostiukevich, V. M.; Stasiuk, V. A.; Shchepotina, N. Y.; Dyachenko, A. A. (Physical Education of Students, 2017)
Purpose: of the research is to prove experimentally the skilled football players training process in the annual macrocycle on the basis of programming. Material: the skilled football players participated in a research (n=20, age 18-23 years). Control provided use of the following tests: 30 m run; shuttle run 7x50 m; long jump from the spot; Cooper`s test. Results: programs of training microcycles were developed. In each program such components of the training were considered: value and orientation of loads; means (non-specific and specific); modes of coordination complexity of exercises performance; training time; time for renewal of competition form, theoretical and psychological preparation; load coefficient value; intensity of training load coefficient. Conclusions: Programming of training process has to be carried out on the basis of systemically structural approach: the development of programs of less structural formations has to be subordinated to the main structural formations. The structure of microcycles includes programs of trainings. Programs of stages consist of a series of training microcycles programs. The program of a training cycle unites all structural formations. Keywords: training process, football players, planning, programming, macrocycle.